Campanhas publicitárias do programa "Leia para uma Criança" do Itaú Social: uma abordagem investigativa sobre a educação da infância - Diniz, Kênia Mendonça (2019)
The present work searches the ways in which the notions of childhood and of children are present in media artifacts, evidently, in Itaú Bank`s business advertisement pieces. For this, four business advertisement pieces are elected, which take part in a same project, Itaú Children, entitled “Read for a child”, namely: Happy End (2014), Hero (2015), Everybody read together – the world changes like this (2016) and Astronaut (2017). Happy End, the first advertisement piece analyzed, has as narrative`s protagonist a girl that gets in the enclosure of a castle and she is holding a toy box. During her walking until the throne, on a big blue carpet with gilded borders, she finds the princess and, after that, in story, she meets the prince too, whom transformed from toad to human. Hero, the second advertisement piece analyzed, has as a theme the story`s King Arthur, in which there is a knight that passes through valleys and mountains until arrives to a village, where the sword “Scalibur” is localized. He walk until the stone where the sword is spiked. It is a thriller moment because everybody believe he will withdraw it there; nevertheless, this do not occur due to a father of nowadays gets in the enclosure of the medieval story, in company of his son, and is he who achieves removing the sword of the stone, which transforms itself in a book when he lifts it. Everybody read together. The world changes like this, the third advertisement piece analyzed, has as central theme the song “Everybody read together”, in which there are images that dialogue directly with the music`s letter; a magical universe full of magic and enchantment where the children like to be. Astronaut, the fourth business piece advertisement analyzed, has as a protagonist an adult woman, whose the profession is astronaut. During the advertisement piece, this woman has several flashes of her childhood, in which she recognizes she has gained a children`s book that was telling the stars` story. It is able to comprehend that was, by means of reading of this book, in her childhood, in company of her parents that ensures her to choose the profession in which she operates. When there are the analyzing of the four Itaú Bank´s business advertisement pieces, especially lining up imagery texts with oral and written texts, it is clear that these ones complement themselves in a dialogue of convincing that involves the mark Itaú in effort of proving that the objectives that surround it is not just financial, however - mainly – social. This attempting of Itaú mark noble, responsible and engaged, for us, it was the most evident element in advertisement pieces analyzed. The feature of the proposed mark is not just whose a company, but whose an institution worried with the children of the country, worried with the culture and with the development of the children; after all, the divulged campaign is about the reading of books in childhood, with the distribution of children`s books freely. There are background issues very valued in the contemporized world, what become the advertisement text convinced and difficult to be questioned as regard at its premises. However, there is pseudo-concern of Itaú Bank, considering that the reading campaign proposed by this banking institution has an intentionality, which overcome social objectives, exclusively, pervading business goals, in trying of divulging its mark; nevertheless, a mark is not coupled up just with business questions, whereas the Itaú Bank is worried about divulge the imagery of a company more humanized, it is the education one of its priorities.